2002
DOI: 10.1007/s002090100351
|View full text |Cite
|
Sign up to set email alerts
|

Syntomic cohomology as a p -adic absolute Hodge cohomology

Abstract: The purpose of this paper is to interpret rigid syntomic cohomology, defined by Amnon Besser [Bes], as a p-adic absolute Hodge cohomology. This is a p-adic analogue of a work of Beilinson [Be1] which interprets Beilinson-Deligne cohomology in terms of absolute Hodge cohomology. In the process, we will define a theory of p-adic absolute Hodge cohomology with coefficients, which may be interpreted as a generalization of rigid syntomic cohomology to the case with coefficients. (2000):14F30, 14G20 Mathematics Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…The guiding idea here was that just as Selmer groups classify extensions in certain categories of "geometric" Galois representations their higher dimensional analogs -syntomic cohomology groups -should classify extensions in a category of "p-adic motivic sheaves". This was shown to be the case for H 1 by Bannai [1] who has also shown that Besser's (rigid) syntomic cohomology is a p-adic analog of Beilinson's absolute Hodge cohomology [2].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…The guiding idea here was that just as Selmer groups classify extensions in certain categories of "geometric" Galois representations their higher dimensional analogs -syntomic cohomology groups -should classify extensions in a category of "p-adic motivic sheaves". This was shown to be the case for H 1 by Bannai [1] who has also shown that Besser's (rigid) syntomic cohomology is a p-adic analog of Beilinson's absolute Hodge cohomology [2].…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, S is a Tate Ω-spectrum because each S (r) is h-local and A 1 -local, and the map obtained by adjunction from σ r is a quasi-isomorphism because of the projective bundle theorem for P 1 (an easy case of Proposition 5.2). Now, by definition of DM h (K, Q p ) and because of property (DM1) above, for any variety X, and any integers (i, r), we get: For points (1) and (2) Remark B.5. Note that the construction of the syntomic ring spectrum S in DM h (K, Q p ) automatically yields the general projective bundle theorem (already obtained in Prop.…”
Section: Syntomic Regulatorsmentioning
confidence: 97%
See 3 more Smart Citations